El gas somero en los sedimentos de la Ría de Muros-Noia (NO de España): formas de aparición y cartografía - Magariños Álvarez, J.; García Gil, S.; Vilas, F. (Journal of Iberian Geology, 2002)
High-resolution seismic reflection and side-scan sonar records have been analysed and interpreted in order to detect shallow gas signatures in the Ría de Muros-Noia (NW Spain). The different gas features have been classified into four types according to their specific seismic signatures: 1) acoustic blankings s.s., with a flat top surface and kilometric extent, 2) acoustic curtains, with a convex top surface and some tens of meters of lateral extent, 3) acoustic columns, with an enhanced reflector at the top and an averaged extent of 20 m, and 4) acoustic turbidity, distinguishable as a diffuse perturbation of the records. At the same time, two different types of gas escape features have been also distinguished: a) acoustic plumes into the water column, rising up to 10 m above the present seafloor, and b) pockmarks on the present seabed, recognised as highly reflective areas in the side-scan sonar records. Mapping of acoustic blankings s.s. reveals the presence of a large gas field (11.5 km2) in the inner part of the ría. In this field the top of the gas accumulates from the close seabed surface up to 4 ms TWT (3.2 m) in depth. Moreover a map with the spatial distribution of the gas accumulations and of the gas escape features is shown.